2014
DOI: 10.1680/geolett.14.00010
|View full text |Cite
|
Sign up to set email alerts
|

A generalised failure envelope for undrained capacity of circular shallow foundations under general loading

Abstract: This paper presents a generalised failure envelope for the prediction of the undrained capacity of circular shallow foundations under general vertical, horizontal and moment (VHM) loading. Uniaxial capacities and failure envelopes under combined loading are presented for shallow circular foundations over a practical range of embedment ratio and soil strength heterogeneity. An approximating expression is proposed to describe the shape of the normalised VHM failure envelope as a function of foundation embedment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
43
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(44 citation statements)
references
References 30 publications
0
43
1
Order By: Relevance
“…strip, circular and rectangular) have been derived using plasticity analysis and finite element analyses [68,[70][71][72][73]. In these studies unlimited tensile strength was assumed for the interface (i.e.…”
Section: Gravity Basesmentioning
confidence: 99%
See 1 more Smart Citation
“…strip, circular and rectangular) have been derived using plasticity analysis and finite element analyses [68,[70][71][72][73]. In these studies unlimited tensile strength was assumed for the interface (i.e.…”
Section: Gravity Basesmentioning
confidence: 99%
“…Taiebat and Carter [72] found that the position of the maximum moment in H-M plane shifts towards the moment axis with increasing vertical loading. In practical engineering, foundations could be shallowly embedded in non-uniform soils and the corresponding failure envelopes were presented by Bransby and Randolph [76] for strip foundations and Vulpe et al [73] for circular foundations, to account for the embedment ratio and soil strength heterogeneity. The thin surficial crust which arises in many deep-water locations could affect the failure envelope much.…”
Section: Gravity Basesmentioning
confidence: 99%
“…Fig. 6(a) shows the normalised failure envelopes in the HM load plane at V/V max = 0·5 computed by HVMCap (this study) and the envelopes from former studies (Gourvenec, 2008;Vulpe et al, 2014;Ntritsos et al, 2015). The strip and square representations in the referred studies had an aspect ratio of h/B = 0·5, where B is the width of the foundation.…”
Section: Verification Of Feamentioning
confidence: 99%
“…The properties of failure envelopes for skirted foundations have been investigated extensively in a number of experimental and numerical studies. The studies have considered how the shape and size of the failure envelopes are affected by the embedment depth, foundation geometry, shear strength profile, undrained and drained conditions, deformable and non-deformable soil plug and limited interface shear and tension strength (Jostad et al, 1994;Martin, 1994;Ukritchon et al, 1998;Taiebat & Carter, 2000;Villalobos, 2006;Gourvenec, 2008;Bransby & Yun, 2009;Randolph & Gourvenec, 2011;Vulpe et al, 2014;Gerolymos et al, 2015;Ntritsos et al, 2015;Vulpe, 2015). The present numerical study considers the undrained response of circular skirted foundations in clay subjected to combined static and cyclic general loading.…”
Section: Introductionmentioning
confidence: 99%
“…Only few studies were performed by considering the 33 caisson foundation using three-dimensional model. Most of these analyses did not 34 comprehensively covered a wide range of practical embedment ratios or investigate all 35 vertical, horizontal and moment bearing capacities [21][22]. A summary of previous 36 studies on undrained bearing capacities and failure envelopes of shallow foundations are 37 presented in Table 1.…”
Section: Introductionmentioning
confidence: 99%